2013
DOI: 10.1002/ajmg.c.31369
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of ventricular trabeculation/compaction and the pathogenesis of the left ventricular noncompaction cardiomyopathy (LVNC)

Abstract: Ventricular trabeculation and compaction are two of the many essential steps for generating a functionally competent ventricular wall. A significant reduction in trabeculation is usually associated with ventricular compact zone deficiencies (hypoplastic wall), which commonly leads to embryonic heart failure and early embryonic lethality. In contrast, hypertrabeculation and lack of ventricular wall compaction (noncompaction) are closely related defects in cardiac embryogenesis associated with left ventricular n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
123
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 105 publications
(171 reference statements)
2
123
0
3
Order By: Relevance
“…Because ventricular trabeculation and myocardial compaction are 2 essential steps necessary for a fully functional and competent ventricular wall, we investigated whether NSML mutations affected initiation of trabeculation. Normally, at E10.5, the myocardium begins to thicken, mediating endocardial cell invagination and formation of trabecular protrusions (6). Here, we found that the trabecular area for both Shp2 Y279C/+ and Shp2 Y279C/Y279C embryos was significantly decreased as compared with WT ( Figure 3, D and F), suggesting a defect in onset of myocardial development.…”
Section: Shp2mentioning
confidence: 54%
See 1 more Smart Citation
“…Because ventricular trabeculation and myocardial compaction are 2 essential steps necessary for a fully functional and competent ventricular wall, we investigated whether NSML mutations affected initiation of trabeculation. Normally, at E10.5, the myocardium begins to thicken, mediating endocardial cell invagination and formation of trabecular protrusions (6). Here, we found that the trabecular area for both Shp2 Y279C/+ and Shp2 Y279C/Y279C embryos was significantly decreased as compared with WT ( Figure 3, D and F), suggesting a defect in onset of myocardial development.…”
Section: Shp2mentioning
confidence: 54%
“…Specifically, cell-cell communication occurs between cardiac mesoderm progenitors, neural crest-derived cells, and pharyngeal endoderm to regulate heart tube elongation, looping, and morphogenesis of the OFT (4). In addition, crosstalk between endocardium and myocardium occurs to control both the formation of cardiac valves (5) and ventricular cardiomyocyte differentiation and proliferation (6).…”
Section: Introductionmentioning
confidence: 99%
“…Trabeculation initiates at E9.0-9.5 and myocardial compaction occurs at ~E14.5 (Samsa et al, 2013;Zhang et al, 2013). Lack of trabeculation causes embryonic lethality in mice and excess trabeculation causes cardiomyopathy and heart failure in humans (Jenni et al, 1999;Weiford et al, 2004;Breckenridge et al, 2007).…”
Section: Nfps Regulate Ventricular Trabeculation and Compactionmentioning
confidence: 99%
“…Cessation of compaction results in a bilayered myocardium consisting of a compacted epicardial and a non-compacted subendocardial layer. Recent findings from genetically-engineered mice have clarified partially the molecular mechanism of myocardium development and its derangements 2,3 . It is recognized that, although 'normal' hypoxia is essential for heart formation, further abnormal hypoxia in utero adversely affects cardiogenesis 4 .…”
mentioning
confidence: 99%
“…Animal experiments have demonstrated that a thin compact myocardium with persistence of prominent subendocardial trabeculation, very similar to human NCVM, may be a result of embryonic hypoxia 5 . It is possible that hypoxic stress, in a critical period of development, promotes adaptive modifications in the complex genetic pathways responsible for myocardial development, such as those common to the thin compacted myocardium of engineered embryos and human NCVM 3 …”
mentioning
confidence: 99%